The Influence of Accessibility and WOM on Visitation Interest in Dewi Kenangan Ponokawan Village Krian Sidoarjo - Firdanti Allivia Syahputri; Fedianty Augustinah; Andry Herawati (Cita konsultindo, 2024)
This study aims to analyze the influence of accessibility and Word of Mouth (WOM) on visitation interest in the Food Security Tourism Destination (Dewi Kenangan) in Ponokawan Village, Krian, Sidoarjo. The research employs a quantitative method with a survey approach. The sample for this study consists of 169 respondents selected using Simple Random Sampling. Data were collected through a questionnaire measuring three main variables: accessibility, word of mouth, and visitation interest. The measurements were conducted using a 5-point Likert scale. Data analysis was performed using multiple linear regression with the help of SPSS version 24 software. The results show that accessibility and WOM have a significant influence on visitation interest, both partially and simultaneously. The accessibility variable has a positive and significant effect on visitation interest, with a regression coefficient value of 0.660 and a t-count value of 6.848. The WOM variable also has a positive and significant effect on visitation interest, with a regression coefficient value of 1.051 and a t-count value of 6.970. Simultaneously, these two variables contribute 64.4% to the variation in visitation interest. This study concludes that improving accessibility and WOM can increase tourists' interest in visiting the Kenangan Tourism Destination in Ponokawan Village. Therefore, tourism destination managers need to consider these factors in their destination development and marketing strategies.